1934 Ky. Acts 169-70, An Act . . . prescribing punishment for robbery or burglary . . ., ch. 52, § 1159(a). - (:unkn) unknown (General Publisher, 1934)
That if any person shall commit acts of robbery, burglary . . . robbery of bank [sic] or safe, and in committing said act or acts shall use or display any pistol, gun or other firearms or deadly weapon of any character in so doing; upon conviction such person or persons shall be sentenced to death or life imprisonment in the discretion of the jury
--
Keywords: COMMITTING CRIME W/ WEAPON